Exit : South Africa's gay and lesbian newspaper. (Johannesburg : Highland Publications, 1991)
Fonds Suzan Daniel (FSD)
Periodiciteit: maandelijks
Redactie: PO Box 18817 Kensington 2101
Engels
Periodiek